Association of hypokalemic periodic paralysis with cystic Kidney disease- A case report - Mehta, Ricken; Thomas, David Mathew; Ramakrishna, Vedavathi; Chikkananjaiah, Sanjay Senaba; Rudraswamy, Chandrashekhar Hosadurga (Asian Journal of Medical Sciences, 2017)
Hypokalemic periodic paralysis (HPP) is a rare heterogenous neuromuscular disorder presenting with acute weakness. Though most cases are known to be familial or primary there are other underlying secondary causes which require evaluation and if not corrected could lead to recurrent episodes.Distal renal tubular acidosis (RTA) is one such association which has been described. Type 1/Distal RTA is known to cause renal potassium wasting thereby leading to hypokalemia. Patients with Distal RT A are unable to acidify their urine. The causes of Distal RTA can be hereditary, congenital, acquired or idiopathic. Severe hypokalemia with RTA has been described along with Medullary sponge Kidney and other cystic lesions in the kidney. There have been previous reports of hypokalemic paralysis occurring secondary to RT A precipitated by cystic kidney disease. We hereby report one such of hypokalemic periodic paralysis secondary to distal RTA which was associated with cystic kidney disease. Asian Journal of Medical Sciences Vol.8(4) 2017 57-59